Pattern of hearing loss among patients visiting ENT OPD at Janaki Medical College: A cross sectional study (Janaki Medical College Journal of Medical Science, 2017)
Background and Objectives: To study the pattern of hearing loss among patients visiting ENT OPD in Janaki medical college teaching hospital.Material and Methods: The study was conducted in department of ENT- head and neck surgery in Janaki medical college teaching hospital from June to December 2016. All the clinically diagnosed cases Demographic data and PTA assessment were taken. with hearing impairment were enrolled in the study and hearing assessment done.Results: Total of 119 patients were enrolled. Among them, male were 58(48.7%) and female 61(51.3%). In age distribution, commonly affected age group was 21-30 years followed by 31-40 years group.On comparing hearing level between both the ears, right ear was having mean hearing threshold of 45.4454 dB and left ear having 47.3277 dB with standard deviation 16.54665, 15.98363 respectively. The difference between both the values is statistically not significant (p value- 0.165). On evaluating type of hearing loss between both the ears, there were almost similar frequencies of hearing loss pattern (p value- 0.190).Out of 119 patients, 20(8.4%) were having unilateral hearing loss. So total of 218(91.6%) ears were affected out of 238 ears. Among them 116(48.8%) ears had conductive hearing loss, 30(12.6%) ears had sensori-neural hearing loss and 48(20.2%) ears had mixed hearing loss.On evaluating degree of hearing loss, patients were mostly having mild hearing loss (41.2%) followed by severe hearing loss (25.2%), moderate hearing loss (24.4%). There was almost similar degree of hearing loss in both the ears with statistically insignificant (p value- 0.379).Conclusion: Hearing impairment commonly involved female with younger population involvement. Hearing impairment was mostly conductive type. Hearing loss was mostly mild degree and bilateralism is common.